Bibliometric analysis using R package on sustainable entrepreneurship studies - Abdullah, Mohd Amli; Abdul Kadir, Mohd Ali Bahari; Ahmad, Badli Esham (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
Entrepreneurship is widely acknowledged as a driver of long-term development and prosperity. Entrepreneurship research has made major contributions in a variety of fields. It has investigated the determinants of entrepreneurship from the individual to the national level. In this study, a quantitative approach is used to provide valuable insights into citation patterns, co-citation analysis, and the intellectual structure of a research domain to gain an understanding of the existing literature, aiding in furthering knowledge and identifying gaps for future research. Scopus is the database used, and the bibliometric application used is Biblioshiny, a bibliometrics analysis R package. The search was restricted to items published in English between 1997 and 2023. The program detected 501 documents from 237 sources, with an annual growth rate of 11.99 percent, an average of 4.67 publications per year, 778 keywords-plus (ID), 1248 author keywords (DE), and 1190 authors. Furthermore, there are 82 authors of single-authored documents, 2.8 co-authors per document, and a 26.35 rate of international collaboration. In addition, the topic growth rate was 11.99, the highest scientific output was 2022, the top publication is a Sustainability publication, the most relevant author is Zhang Y, and the highest cited country is Germany. With this information, future studies can be used to identify which perspective of sustainable entrepreneurship will be explored.